Outcomes of an individual counselling programme in Grozny, Chechnya: a randomised controlled study. Issue 8 (23rd August 2018) - Lenglet, Annick; Lopes-Cardozo, Barbara; Shanks, Leslie; Blanton, Curtis; Feo, Concetta; Tsatsaeva, Zalina; Idrisov, Kyuri; Bolton, Paul A; Pintaldi, Giovanni
Abstract : Objectives: To evaluate the effectiveness of individual counselling on functioning of clients participating in a mental health intervention in a humanitarian setting. Design: Randomised controlled trial. Setting: Mental health programme implemented by Médecins Sans Frontières in Grozny, Republic of Chechnya. Participants: 168 eligible clients were randomly assigned to the intervention and waitlisted (2 months) arms between November 2014 and February 2015. Intervention: Individual counselling sessions. Main outcome measures: Change in functioning was measured using the Short Form 6 (SF6) and gender-specific locally adapted Chechen functioning instruments in the intervention group at the end of counselling and the waitlisted group after their waitlisted period. Unadjusted differences in gain scores (DGSs) between intervention and waitlisted groups were calculated with effect size (Cohen's d ) for both tools. Linear regression compared the mean DGS in both groups. Results: The intervention group (n=78) improved compared with waitlisted controls (n=80) on the SF6 measures with moderate to large effect sizes: general health (DGS 12.14, d =0.52), body pain (DGS 10.26, d =0.35), social support (DGS 16.07, d =0.69) and emotional functioning (DGS 16.87, d =0.91). Similar improvement was seen using the Chechen functioning instrument score (female DGS −0.33, d =0.55; male DGS −0.40, d =0.99). Adjusted analysis showed significant improvement (p<0.05) in the intervention group for all SF6 measures and for the Chechen functioning instrument score in women but not men (p=0.07). Conclusions: Individual counselling significantly improved participants' ability to function in the intervention group compared with the waitlisted group. Further research is needed to determine whether similar positive results can be shown in other settings and further exploring the impact in male clients' population. Trial registration number: NTR4689.